Evaluating the clinical feasibility: the direct bisulfite genomic sequencing for examination of methylated status of protocadherin10 (PCDH10) promoter to predict the prognosis of gastric cancer - Ya-Chao Hou; Han Liang (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: To elucidate the clinical significance of the methylated status of CpG site count of PCDH10 promoter in the survival prediction in gastric cancer (GC). Methods: In our previous study, we demonstrated that the methylated CpG site count was significantly associated with the survival of patients with gastric cancer using the bisulfite genomic sequencing (BGS) in the gastric cancer tissue with five clones per sample. It was so complicate for each patient underwent the BGS detection with clones. Results: PCDH10 promoter methylation was found 257 (54.6%) in all patients. GC patients with 5 or more methylated CpG site counts of PCDH10 promoter was significantly associated with poorer survival (P=0.039). On the multivariate survival analysis, we found that T stage, N stage and hypermethylated CpG site counts of PCDH10 DNA promoter were the independent predictors of prognosis for GC patients. Conclusion: Our present findings suggested that hypermethylated CpG site counts of PCDH10 DNA for evaluating the prognosis of gastric cancer was reasonable by using the direct sequencing.